The Development of the Rheumatology Informatics System for Effectiveness Learning Collaborative for Improving Patient‐Reported Outcome Collection and Patient‐Centered Communication in Adult Rheumatology. Issue 10 (20th July 2021) - Subash, Meera; Liu, Lucy H.; DeQuattro, Kimberly; Choden, Sonam; Jacobsohn, Lindsay; Katz, Patricia; Bajaj, Puneet; Barton, Jennifer L.; Bartels, Christie; Bermas, Bonnie; Danila, Maria I.; Downey, Christina; et al.
Abstract : Objective: Patient‐reported outcomes (PROs) are an integral part of treat‐to‐target approaches in managing rheumatoid arthritis (RA). In clinical practice, however, routine collection, documentation, and discussion of PROs with patients are highly variable. The RISE LC (Rheumatology Informatics System for Effectiveness Learning Collaborative) was established to develop and share best practices in PRO collection and use across adult rheumatology practices in the United States Methods: The goals of the RISE LC were developed through site surveys and in‐person meetings. Participants completed a baseline survey on PRO collection and use in their practices. RISE LC learning sessions focused on improving communication around PROs with patients and enhancing shared decision‐making in treatment plans. During the coronavirus disease 2019 (COVID‐19) pandemic, the RISE LC pivoted to adapt PRO tools for telehealth. Results: At baseline, all responding sites (n = 15) had established workflows for collecting PROs. Most sites used paper forms alone. PRO documentation in electronic health records was variable, with only half of the sites using structured data fields. To standardize and improve the use of PROs, participants iteratively developed a Clinical Disease Activity Index–based RA Disease Activity Communication Tool to solicit treatment goals and improve shared decision‐making across sites. The COVID‐19 pandemic necessitated developing a tool to gauge PROs via telehealth. Conclusion: The RISE LC is a continuous, structured method for implementing strategies to improve PRO collection and use in rheumatological care, initially adapting from the Learning Collaborative model and extending to include features of a learning network. Future directions include measuring the impact of standardized PRO collection and discussion on shared decision‐making and RA outcomes.